Characterization of the complete chloroplast genome of medicinal plant Rheum officinale (Polygonaceae) - Li, Yimin (Mitochondrial DNA B Resour, 2019)
The complete chloroplast (cp) genome of Rheum officinale Baill. was determined based on the Illumina Sequencing data. The cp genome is 161,563 bp in length. The overall G + C content of the cp genome was 37.31%. The R. officinale cp genome contains 129 genes, including 84 protein-coding genes, eight rRNA genes (four rRNA species), and 37 tRNA genes (20 tRNA species). A neighbour-joining phylogenetic tree clarified that the cp genome of R. officinale was closely related to that of R. palmatum in Polygonaceae.